Tinjauan Historis dan Sosiologis Perkembangan Kurikulum Pendidikan Agama Islam di Indonesia - Ananda, Ria Rizki; Fatonah, Siti (Lembaga Yasin AlSys, 2022)
The curriculum in Indonesia has undergone several changes in its journey. Curriculum changes aim to improve the education system by maintaining good values on concepts that existed in old education and adding new and better concepts. This research discusses the history of the development of Islamic religious education programs in Indonesia. This research aims to describe how the history of the development of Islamic religious education curriculum in Indonesia, sociological review of curriculum development and factors that influence the development of Islamic education curriculum in Indonesia. This research belongs to the category of library research that is research using articles and books as data sources. The results showed the history of the development of islamic education curriculum in Indonesia from the curriculum in 1947 to the 2013 curriculum. The development of curriculum in Indonesia is strongly influenced by sociological factors, namely customs, beliefs, values, languages, religions, and social institutions.